National research on the postgraduate student experience : case presentation : volume 3 : career development and employability. - Kinash, Shelley; Crane, Linda; Bannatyne, Amy; Judd, Madelaine-Marie; Stark, Ashley; Eckersley, Bill; Hamlin, Gary; Partridge, Helen; Udas, Ken (Office of Learning and Teaching, 2016)
This is volume three of a set of case studies that aim to enhance the postgraduate student experience. The theme of this case study is career development and employability. The other case studies in this series are: 'Volume 1 - First year postgraduate student experiences' and 'Volume 2 - Postgraduate student diversity'. This case study presentation on career development and employability is based on student engagement breakfasts, interviews and focus groups with 366 people across the stakeholder groups of postgraduate students, educators and university executives from 26 Australian institutions. Three overall recommendations emerged from the research and are detailed in this case presentation and sub-divided into specific recommendations for postgraduate students, educators and university leaders. It is recommended that: (1) employability is embedded in the everyday postgraduate curriculum and assessment; (2) employability is made explicit to postgraduate students; and (3) postgraduate studies actively engage with industry to facilitate practical experiences. [VOCED]